Effectiveness Test Of Tobacco Leaves Extract in Resolving Growth of Colletotrichum gloeosporiodes and Lasiodiplodia theorobromae - Desi Yantirukma Sari (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2020)
Tobacco plants is one of the abundant plants in Indonesia with production reaching 197.250 tons by 2019. The use of tobacco plants is generally limited to the leaf portion used for making cigarettes. It poses a serious thread to the healt of the human body as well as the environment. Use of tobacco leaves as vegetable fungicides can be used as an alternative to combating fungal attack on agricultural commodities. One cause of agricultural commodity damage is the decomposition caused by the fungus of C. gloeosporioides and L. theorobromae attack. The research aims to learn the effects of the extract of tobacco leaves on the growth of the mold C. gloeosporioides and L. theorobromae, learn to know the minimum concentration of inhibition (KHM) and the minimum killing concentration (KBM) of tobacco leaves on the mold C. gloeosporioides and L. theorobromae. The research used a complete randomized design with a reated trial of 3 times. The results showed that the extract of tobacco leaves no significant impact in hinting the growth of the mold C. gloeosporioides and L. theorobromae. Minimum concentration testing of tobacco leaves (KHM) shows that the extract of 50% concentration of tobacco leaves is KHM of the C. gloeosporioides and L. theorobromae. The extract of 100% concentrated tobacco leaves is the minimum kill concentrate (KBM) of L. theorobromae. Minimum kill concentration of fungus C. gloeosporioides cannot be determined. Keywords: Tobacco, Vegetable Fungicides, Flavonoid, Antifungal